2022
DOI: 10.1002/uog.24795
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of model for prediction of placental dysfunction‐related stillbirth from maternal factors, fetal weight and uterine artery Doppler at mid‐gestation

Abstract: What are the novel findings of this work?Screening at mid-gestation by a combination of maternal risk factors, estimated fetal weight (EFW) and uterine artery pulsatility index (UtA-PI) can predict a high proportion of placental dysfunction-related stillbirths and, in particular, those that occur preterm. Such screening provides poor prediction of unexplained stillbirth or stillbirth due to other causes. The predictive performance for placental dysfunction-related stillbirth in a validation dataset was consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…Gestational age was determined from measurement of fetal crown–rump length at 11–13 weeks or the fetal head circumference at 19–24 weeks of gestation 13,14 . The same study population was used for development and validation of the model based on multivariable logistic regression analysis for prediction of placental dysfunction related stillbirth 1 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gestational age was determined from measurement of fetal crown–rump length at 11–13 weeks or the fetal head circumference at 19–24 weeks of gestation 13,14 . The same study population was used for development and validation of the model based on multivariable logistic regression analysis for prediction of placental dysfunction related stillbirth 1 …”
Section: Methodsmentioning
confidence: 99%
“…The distributions of patient‐specific risks were used to estimate detection rates and FPR from analysis of receiver operating characteristic (ROC) curves. Similarly, patient‐specific risks were estimated using our previously reported logistic regression model for placental dysfunction related stillbirth 1 . The predictive performance for stillbirth of the competing risks model for SGA 7 and the stillbirth‐specific logistic regression model for placental dysfunction 1 was compared by the area under the ROC curve with 95% CI and by the detection rate with 95% CI at 10% FPR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study involving 131,514 of the pregnancies included in the current study, we reported that 92% of stillbirths were antepartum and 8% were intrapartum. About 60% of the antepartum stillbirths were thought to be due to impaired placentation, because the fetuses were small-for- gestational-age and/or the women had developed pre-eclampsia, and the other 40% were due to other causes or were unexplained [ 39 ]. Multivariable regression analysis showed that significant contribution to increased risk of impaired placentation-related stillbirths was provided by Black race, increasing body mass index, cigarette smoking, chronic hypertension, and previous pregnancy complicated by stillbirth, or preeclampsia or birth of small-for-gestational-age neonate.…”
Section: Discussionmentioning
confidence: 99%
“…Stillbirth constitutes a major tragedy in obstetrics and unfortunately, with current prenatal care many cases are unpredictable and, therefore, not preventable. However, extensive evidence suggests that first, about 60% of antepartum stillbirths are observed in association with placental dysfunction [ 17 ], and second, more than half of such stillbirths can be effectively identified in the first trimester based on screening by a combination of maternal characteristics, maternal serum PAPP-A, the uterine artery pulsatility index (UtA-PI), and the ductus venosus pulsatility index [ 18 , 19 ].…”
Section: Screening For Stillbirthmentioning
confidence: 99%